Comparing the effects of ramp metering and variable speed limit on reducing travel time and crash risk at bottlenecks. Issue 2 (6th December 2017) - Li, Zhibin; Xu, Chengcheng; Li, Dawei; Liu, Pan; Wang, Wei
Abstract : Ramp metering (RM) and variable speed limits (VSLs) affect freeway traffic in different ways and, accordingly, result in different effects on travel time and crash risk. This study compared the effects of RM and VSL at different freeway bottleneck segments with various traffic demands. An isolated merge bottleneck segment was examined, and then extended to consider closely spaced upstream ramps and downstream diverge bottleneck. Two control strategies were tested which were the Asservissement LINéaire d'Entrée Autoroutiére (ALINEA)/Q and feedback‐based VSL. The reductions of travel time and crash risk were evaluated using the modified cell transmission models. The results showed that ALINEA/Q was more stable than the feedback VSL, but its power was limited by ramp space. A coordinated RM and VSL strategies were proposed to improve the control effects. The authors also evaluated how traffic demand features on mainline and ramps affected the control effects. The results highlighted the importance of consideration of geometrical features and traffic demands on freeways when selecting the best control strategy.